The nutritional composition of mayonnaise and salad dressing in the Malaysian market - Aswir Abd Rashed,; Mohd Fairulnizal Md Noh,; Norhayati Mustafa Khalid,; Nurul Izzah Ab Rahman,; Afida Tasirin,; Wan Sulong Wan Omar,; Mohd Naeem Mohd Nawi,; Mohd Azerulazree Jamilan,; Rusidah Selamat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Mayonnaise and salad dressing are fast becoming popular condiments for Malaysian. The aim of this study was to obtain the nutritional composition of mayonnaise and salad dressing commercially available in the Malaysian market. The data will be used to update the Malaysian Food Composition Database which was last updated in 1997. A total of six brands from each type of mayonnaise and salad dressing were sampled from local supermarkets in the Klang Valley and analysed using standard methods. The validity of test data was monitored with the application of internal quality controls in line with the requirements of ISO 17025. The energy contents of mayonnaise and salad dressings were up to 626.40 kcal/100 g. Our findings were also in agreement with the energy labelling on the packaging. Sodium was high in mayonnaise and salad dressing because it is used in the final mixture of both condiments to improve their characteristics for certain reasons. Mayonnaise and salad dressing have been identified as potent sources of vitamin A and vitamin E and both condiments were found to contain high levels of these antioxidants. It can be concluded that this study are useful not only in providing information on the nutritional content of several commercial types of mayonnaise and salad dressing, but also in improving the public understanding of healthy food choices.